ASSA14-01-02 Circulating Platelet-Leukocyte Aggregates: a Sensitive Marker of No-reflow in Acute Myocardial Infarction Patients. (1st December 2014) - Dong, M; Mu, N; Ren, F; Sun, X; Yang, J
Abstract : Objective: We investigated whether elevated levels of circulating platelet-leukocyte aggregates (PLA) can be used to identify acute myocardial infarction patients with no-reflow. Methods: 120 patients with acute myocardial infarction (AMI) (72 male/48 female, mean age: 65.6 ± 8.6 years), undergoing successfully percutaneous coronary intervention (PCI), were studied and their PLA was measured by flow cytometry. PLA were identified as platelet-neutrophil aggregates (PNA) and platelet-monocyte aggregates (PMA). No-reflow was defined as a coronary TIMI flow grade ≤ 2 after vessel reopening or TIMI flow 3 with a final MBG ≤ 2. Blood samples were obtained before PCI. Logistic regression models were developed with adjustment for confounders. Result: Compared with normal reflow group (n = 95), no-reflow group (n = 25) had significantly higher counts of circulating PNA (p < 0.001) and PMA (p < 0.001). In univariable logistic regression models, diabetes mellitus, lesion length, reference luminal diameter, thrombus score ≥ 4, circulating levels of PNA and PMA were all found to be positively associated with the risk of no-reflow (p < 0.05). After adjusting for these factors, circulating levels of PNA (OR 4.156, 95% CI : 2.435–8.168; p = 0.006) and PMA (OR 5.132, 95% CI: 2: 135–7.218; p = 0.007) were found to be independent risk factors of no-reflow together with diabetes mellitus (OR 10.134, 95% CI: 2.234–35.342; p = 0.029). Conclusion: Circulating PLA is a sensitive marker of no-reflow in AMI patients.